Relatório final do estágio curricular obrigatório do curso de medicina veterinária realizado no Hospital Veterinário UEL da Universidade Estadual de Londrina e no Hospital Veterinário Governador Laudo Natel da FCAV - Unesp : caso de interesse: neoplasia mamária em cadela – relato de caso - Rodrigues, Bianca Cardenal Balla [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Com o avanço nos cuidados de saúde animal e a melhoria dos serviços veterinários, a expectativa de vida dos animais aumentou. Com isso, houve um crescimento da incidência de neoplasias. Nas cadelas, as neoplasias mamárias são as mais comuns, representando entre 50% e 70% de todos os casos de câncer em cães, sendo que 35% a 50% são malignos. O presente relatório descreve os locais e as atividades desenvolvidas durante o Estágio Curricular em Práticas Veterinárias, sendo eles no Hospital Veterinário da UEL (Universidade Estadual de Londrina) e no Hospital Veterinário "Governador Laudo Natel" da FCAV -Unesp, além de uma revisão bibliográfica do assunto Neoplasia Mamária em Cadela e um relato de caso.

With advancements in animal health care and improved veterinary services, animal life expectancy has increased. As a result, there was an increase in the incidence of neoplasms. In chains, mammary neoplasms are the most common, representing between 50% and 70% of all cases of cancer in dogs, of which 35% to 50% are malignant. This report describes the locations and activities carried out during the Curricular Internship in Veterinary Practices, namely at the Veterinary Hospital of UEL (State University of Londrina) and at the "Governador Laudo Natel" Veterinary Hospital of FCAV - Unesp, in addition to a bibliographical review on the subject of Mammary Neoplasia in a Dog and a case report.
Final report of the mandatory curricular internship of the veterinary medicine course carried out at the UEL Veterinary Hospital of the State University of Londrina and at the Governor Laudo Natel Veterinary Hospital of FCAV - Unesp: case of interest: mammary neoplasia in a dog – case report
Keywords: Neoplasias; Cães; Neoplasias mamárias